Effective Online Teaching : Training Manual : Foundations and Strategies for Student Success - Stavredes, Tina (San Francisco Jossey-Bass Inc Pub, 2011)
The Trainer's Manual follows the course of the main text and includes overviews, readings, discussion questions, hypothetical scenarios, activities, assignments, and scripts for plugging into an online course management system. It is accompanied by a CD that includes plug and play Breeze presentations for each chapter of the Effective Online Teaching text.
Include Reference
Keywords: Web-based instruction -- Internet in education -- Teaching--Computer network resources